Serving His Country: Wellington's Waterloo Banquets, 1822–52. (27th April 2018) - Reynolds, Luke
Abstract: From 1822 until 1852, the Duke of Wellington hosted an annual banquet to celebrate the allied victory at Waterloo. The dinners, despite only being open to the elite of the officer corps that fought at Waterloo, became one of the most recognizable and long-lasting remembrances of the battle in British society. This article first explores the banquets themselves, and then widens its scope to examine the attention, imitations, and criticism that surrounded them, and argues that the Banquet served a variety of purposes. For those who attended, it was a celebration of their military achievements, both past and present, allowing them to bask in the glory of 1815 in a publicly acceptable way. For the British Army as a whole it functioned as a grand celebration in miniature – a surrogate for national acclaim and a pinnacle event, from which all other Waterloo celebrations drew both pomp and legitimacy. For the nation, the Waterloo Banquet provided an anchor to that battle and the quarter-century of war that preceded it, a conflict which played a crucial role in the development of a national identity and served as the moral and rhetorical basis for British hegemony. Despite the attention Waterloo and the Napoleonic Wars have received, the Banquet remains a relatively unexplored phenomenon, and one that can provide insight into the British understandings of European victory, on political, military, and cultural levels.